Integrating Artificial Intelligence in Information Warfare - Dr. Taha Shabbir; Saeed Memon; Dr. Sabir Ahmed; Bilal Sheikh; Dr. Kehkashan Naz (Research Parks Publishing LLC, 2021)
Little advancement in science and technology offer as much promise for humanity's future as the collection of computer science-enabled skills referred to as artificial intelligence (AI). AI has the potential to improve the health and well-being of people, communities, and nations, as well as to help in the achievement of the United Nations' Sustainable Development Goals (SDGs) agenda for 2030. However, like with previous breakthrough breakthroughs, AI applications have the potential to undermine international peace and security, particularly when integrated into the tools and systems of state military. In recognition of this, UN Secretary-General António Guterres' disarmament agenda, Securing Our Common Future, emphasizes the importance for UN member states to gain a better understanding of the nature and implications of emerging technologies with potential military applications, as well as the importance of maintaining human control over weapon systems. He underlines the growing importance of conversation between governments, civic society, and the commercial sector as a supplement to current intergovernmental mechanisms. This is especially true for AI, which, as an enabling technology, is expected to be incorporated into a wide range of military applications yet is now being researched primarily for non-military, predominantly civilian, uses. Nothing has been accomplished from the perspective of a developed country such as Pakistan. If data's use as a foundation for reporting and storytelling grows, it is critical to find responses to concerns about the use or misuse of data, the skills needed to do so, data journalism platforms and instruments, and potential newsroom changes. This research aims to answer the concerns from Pakistan's perspective. Additionally, it addresses the intellectual turns that Big Data and data journalism take in collecting, processing, explaining, interpreting, and representing reality.